ANALISIS KINERJA GURU BERDASARKAN ASPEK LINGKUNGAN KERJA, KEPUASAN KERJA DAN KEPEMIMPINAN KEPALA SEKOLAH (Studi Kasus SMA Negeri Se-Kabupaten Bireuen) - Yuslina (JURNAL KEBANGSAAN, 2022)
The study was conducted on 270 samples of public high school teachers in Bireuen Regency, using a descriptive analysis approach and verification using the path analysis method. The results of the study based on statistical analysis with a path analysis approach, it is evident from the results of testing the research hypothesis that: 1) there is a direct and indirect influence of the teacher's work environment factors on teacher performance which is very significant, namely 15.80%. 2). there is a direct and indirect effect of teacher job satisfaction on teacher performance that is equal to 27.68%. 3). There is a direct and indirect influence on the leadership aspect of the Principal of Public High Schools in Bireuen Regency on the performance of teachers in schools, which is 7.50%. and 4). The results of the calculation of the correlation coefficient and determination between work environment factors, teacher job satisfaction and school principal leadership showed a simultaneous influence on the performance of public high school teachers throughout Bireuen Regency by 51%.